Participation of the inositol 1,4,5-trisphosphate-gated calcium channel in the zona pellucida- and progesterone-induced acrosome reaction and calcium influx in human spermatozoa - Ying-Ya Li (Asian Journal of Andrology, 2020)
The acrosome reaction is a prerequisite for fertilization, and its signaling pathway has been investigated for decades. Regardless of the type of inducers present, the acrosome reaction is ultimately mediated by the elevation of cytosolic calcium. Inositol 1,4,5-trisphosphate-gated calcium channels are important components of the acrosome reaction signaling pathway and have been confirmed by several researchers. In this study, we used a novel permeabilization tool BioPORTER® and first demonstrated its effectiveness in spermatozoa. The inositol 1,4,5-trisphosphate type-1 receptor antibody was introduced into spermatozoa by BioPORTER® and significantly reduced the calcium influx and acrosome reaction induced by progesterone, solubilized zona pellucida, and the calcium ionophore A23187. This finding indicates that the inositol 1,4,5-trisphosphate type-1 receptor antibody is a valid inositol 1,4,5-trisphosphate receptor inhibitor and provides evidence of inositol 1,4,5-trisphosphate-gated calcium channel involvement in the acrosome reaction in human spermatozoa. Moreover, we demonstrated that the transfer of 1,4,5-trisphosphate into spermatozoa induced acrosome reactions, which provides more reliable evidence for this process. In addition, by treating the spermatozoa with inositol 1,4,5-trisphosphate/BioPORTER® in the presence or absence of calcium in the culture medium, we showed that the opening of inositol 1,4,5-trisphosphate-gated calcium channels led to extracellular calcium influx. This particular extracellular calcium influx may be the major process of the final step of the acrosome reaction signaling pathway.